Hidup di Dunia Multikultural Potret Sosial Budaya Kerukunan Etnis Minang dan Tionghoa di Kota Padang - Rahmi Surya Dewi (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The issue of indigenous and non-indigenous, minorities and the majority has become an exaggerated issue causing the sentiment and the disturbance of relations between ethnic minorities and ethnic majority. This article was intentionally written to see a portrait of harmony between ethnic Minang and Tionghoa in Padang City. Lately it is so easy to insult and degrade the religion of others. Therefore, this article aims to provide awareness to the parties who deliberately divide relations and harmony among tribes, religions, races and groups in Indonesia. One of portraits of inter-ethnic and inter-religious harmony can be seen in West Sumatra. The ability of ethnic Chinese to be ethnic Minang who use matrilineal system by emphasizing the element of motherhood makes the potential of conflict can be minimized. The harmony between the two ethnics could frequently end with inter-ethnic marriage.